A study on determinants of household saving in Asean Countries: Malaysia, Philippines and Thailand / Ahmad Aimi Asyran Ahmad Mazuki - Ahmad Mazuki, Ahmad Aimi Asyran (Faculty of Business and Management, 2020)
Household Saving is the segment of pay that is not being used in current utilizations. The purpose of this study is to observe the determinants of household saving rate that shape the financial situations of a nation in Southeast Asia which are Malaysia, Philippines and Thailand. The factors are deriving from the housing price index denoted by real property index, inflation rate measured by consumer price index, unemployment rate represented by% of total labour force and interest rate measured by % of government bond. The study follows descriptive research using panel data from 2009 until 2018. Final regression model has been chosen as the method to analyse the result. The empirical result shows that all variables have significant relationship towards household saving except housing price index.